The Influence Of Islamic Reading Corners And Reading Interest On Students Reading Literacy In Madrasah Ibtidaiyah - Usaniyah, Robi; Setiyadi, Desi; Miftachudin, Miftachudin (AT-TURATS, 2024)
Nowadays, reading activities have become boring and uninteresting activities for students. One of the schools efforts to foster students' interest in reading is by forming a reading corner in the corner of the classroom. The reading corner in this madrasah ibtidaiyah is decorated with Islamic nuances so students are more active in reading and reminding them that first revelation that Rasullulah got was the command to read. This study aims to analyse the effect of Islamic reading corner and reading interest on reading literacy in madrasah ibtidaiyah. This type of research is a correlation type quantitative research that aims to see the relationship between the variables of Islamic reading corner, reading interest, and reading literacy. The population in this study was in the madrasah ibtidaiyah of the setu cluster, setu sub district, the sample was at MI Nurul Falah Muncul, totalling 54 fourth grade students. The sampling technique in this study used simple random sampling technique and analysis technique in this study used multiple linear regression analysis techniques. The results showed that T test of the Islamic reading corner variable with reading interest had a significant and positive effect on reading literacy. While from the results of the F test, the Islamic reading corner and reading interest have a significant and positive influence on the reading literacy of grade IV students at MI Nurul Falah. Based on these results it can be concluded that the Islamic reading corner and reading interest have an effect on student reading literacy in MI.Dewasa ini kegiatan membaca menjadi kegiatan yang membosankan dan tidak diminati oleh siswa. Maka dari itu salah satu upaya sekolah untuk menumbuhkan minat membaca siswa dengan membentuk pojok baca yang berada di dalam sudut kelas, pojok baca yang berda di madrasah ibtidaiyah ini dihiasi dengan nuansa islami agar siswa semakin giat dalam membaca dan mengingatkan bahwa wahyu pertama yang Rasullulah dapat adalah perintah membaca. Penelitian ini bertujuan untuk menganalisis pengaruh pojok baca bernuansa islami dan minat baca terhadap literasi membaca di madrasah ibtidaiyah. Jenis penelitian ini adalah penelitian kuantitatif tipe korelasi yang bertujuan untuk melihat hubungan antar variable pojok baca bernuansa islami, minat baca, dan literasi membaca. Populasi pada penelitian ini berada di madrasah ibtidaiyah gugus setu kecamatan setu, sampel berada di MI Nurul Falah Muncul yang berjumlah 54 siswa kelas IV. Teknik pengambilan sampel pada penelitian ini menggunakan teknik simpel random sampling. Teknik analisis data pada penelitian ini menggunakan teknik analisis regresi linear berganda. Hasil penelitian menunjukkan yaitu hasil uji T variabel pojok baca bernuansa islami dengan minat baca mempunyai pengaruh signifikan dan positif terhadap literasi membaca. Sedangkan dari hasil uji F pojok baca bernuansa islami dan minat baca mempunyai pengaruh signifikan serta positif terhadap literasi membaca siswa kelas IV di MI Nurul Falah. Berdasarkan hasil tersebut dapat disimpulkan pojok baca bernuansa islami dan minat baca berpengaruh terhadap literasi membaca siswa di MI.